Research Progress on the Inflammatory Effects of Long Non-coding RNA in Traumatic Brain Injury - Wang, Jian-peng; Li, Chong; Ding, Wen-cong; Peng, Gang; Xiao, Ge-lei; Chen, Rui; Cheng, Quan (Frontiers in Molecular Neuroscience, 2022)
Globally, traumatic brain injury (TBI) is an acute clinical event and an important cause of death and long-term disability. However, the underlying mechanism of the pathophysiological has not been fully elucidated and the lack of effective treatment a huge burden to individuals, families, and society. Several studies have shown that long non-coding RNAs (lncRNAs) might play a crucial role in TBI; they are abundant in the central nervous system (CNS) and participate in a variety of pathophysiological processes, including oxidative stress, inflammation, apoptosis, blood-brain barrier protection, angiogenesis, and neurogenesis. Some lncRNAs modulate multiple therapeutic targets after TBI, including inflammation, thus, these lncRNAs have tremendous therapeutic potential for TBI, as they are promising biomarkers for TBI diagnosis, treatment, and prognosis prediction. This review discusses the differential expression of different lncRNAs in brain tissue during TBI, which is likely related to the physiological and pathological processes involved in TBI. These findings may provide new targets for further scientific research on the molecular mechanisms of TBI and potential therapeutic interventions.